2016
DOI: 10.1080/07373937.2016.1160246
|View full text |Cite
|
Sign up to set email alerts
|

Removal behaviors of moisture in raw lignite and moisturized coal and their dewatering kinetics analysis

Abstract: In order to investigate the dewatering kinetics and mechanism of low rank coal, the dewatering behaviors of a Chinese lignite and its moisturized sample (prepared from dewatered coal moisturized under relative humidity of 75% at 303 K for 48 h) in nitrogen and the temperature range of 333-433 K were tested. Physical structure changes of raw coal, moisturized coal before and after drying were determined. The results indicate that drying process of lignite could be divided into four stages, which are increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 26 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Based on the activation energy values and R 2 , models with g (α) = −(ln­(1 – α)) 1/2 were optimum for the increasing-rate and constant-rate stages and models with g (α) = −ln­(1 – α) were optimum for the decreasing-rate stage. We referenced the activation energy values of brown coal drying in other studies. , If the R 2 was very high, but the activation energy was too big or small compared with that in references, then the model would not be used. The acceptable range of activation energies could be 15–45 kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the activation energy values and R 2 , models with g (α) = −(ln­(1 – α)) 1/2 were optimum for the increasing-rate and constant-rate stages and models with g (α) = −ln­(1 – α) were optimum for the decreasing-rate stage. We referenced the activation energy values of brown coal drying in other studies. , If the R 2 was very high, but the activation energy was too big or small compared with that in references, then the model would not be used. The acceptable range of activation energies could be 15–45 kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
“…The apparent diffusion coefficient was calculated by Fick’s second law. The details of the calculation process were presented by our previous study. , where D eff is the effective diffusion coefficient (m 2 /s); L , which represents the diameter of coal particle, was taken as 8.6 × 10 –4 m. The value was estimated by that the percentage of coal particle size smaller than 0.75 mm was approximately 85 wt %. The percentage of coal particle size smaller than 0.75 mm was analyzed by a 200-mesh sieve.…”
Section: Methodsmentioning
confidence: 99%
“…Feng et al investigated the effect of the Mechanical Thermal Expression on the structure of lignite and determined changes in volume of pores between the raw lignite and lignites dried at drying temperatures between 120 • C and 150 • C under pressures of 10 MPa and 30 MPa respectively [10]. Wen et al investigated the drying kinetics of raw and re-moisturised lignite and determined the drying rate of the former was slower in comparison to the latter [11]. Moreover, the study found the effective diffusion coefficient for the moisturised lignite to be higher than a corresponding value for a raw lignite [11].…”
Section: Drying Of Lignitementioning
confidence: 99%
“…Wen et al investigated the drying kinetics of raw and re-moisturised lignite and determined the drying rate of the former was slower in comparison to the latter [11]. Moreover, the study found the effective diffusion coefficient for the moisturised lignite to be higher than a corresponding value for a raw lignite [11].…”
Section: Drying Of Lignitementioning
confidence: 99%
“…The pressure is regarded as the initial pore pressure. During the water-driven-methane process, pressure water will flow along the pore channel [21][22][23][24]. This breaks the original mechanical equilibrium in the coal sample, and the stress is redistributed again.…”
Section: Geofluidsmentioning
confidence: 99%